Age at first reproduction and longest-lived individuals in the Pallid Swift Apus pallidus (Avocetta, 2022)
Swifts are long-living birds with delayed maturation; however, the age at first reproduction and their maximum life span is known for a few species. We discuss here some data about these parameters, using observations collected during our long-standing study on Pallid Swift Apus pallidus in Northern Italy. The longest-lived bird in our dataset was still recovered breeding 19 calendar years after maturity, and the youngest confirmed age at first breeding was 3 years (i.e., bird in 4th calendar year). No breeding attempts have been verified for individuals in their second and third calendar year.
Keywords: Pallid Swift; age first reproduction; longevity; senescence